Analysis of Critical Thinking and Self-regulation in Blended Method, Module-aided, Problem-Based Learning - Santoso, Denni Agung (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
In pandemic conditions, the government has established distance learning online. After the pandemic, the learning process has returned to offline activities. However, the technology used during online learning is available. In such conditions, offline and online learning combination is a necessity for learning in the future. To deal with it is very important for students to have the ability to think critically and learn independently. The purpose of this research is to analyze students' critical thinking skills and learning independence after applying module-assisted problem-based learning. This research was conducted at Muria Kudus University, Kudus Regency. The qualitative research subjects consist of nine students selected from 33 students with low, medium, and high critical thinking abilities. The variables in this study are learning independence and critical thinking skills. Learning independence data was obtained by questionnaire and the critical thinking ability was obtained by a written test. The triangulation process was done by comparing test results, interviews, and observations. The treatment given increases student independence in terms of